2012
DOI: 10.3945/ajcn.112.040485
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of monococcum wheat in celiac patients

Abstract: Our data show that the monococcum lines Monlis and ID331 activate the CD T cell response and suggest that these lines are toxic for celiac patients. However, ID331 is likely to be less effective in inducing CD because of its inability to activate the innate immune pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…Taken together, the studies reported above suggest a favourable safety profile of Tm for CD patients and provide the rationale for testing Tm administration for toxicity in CD patients. It is however noteworthy that, in contrast with previous studies, in vitro toxicity of Tm has been recently reported by Gianfrani et al [12]; such information was not available when we planned our study.…”
Section: Introductionmentioning
confidence: 83%
“…Taken together, the studies reported above suggest a favourable safety profile of Tm for CD patients and provide the rationale for testing Tm administration for toxicity in CD patients. It is however noteworthy that, in contrast with previous studies, in vitro toxicity of Tm has been recently reported by Gianfrani et al [12]; such information was not available when we planned our study.…”
Section: Introductionmentioning
confidence: 83%
“…monococcum wheat showed a marked reduction, or even a lack, of toxicity in vitro cellular assays [13,14]. Gianfrani et al [15] compared the immunological properties of 2 lines of diploid monococcum wheat, Monlis and ID331, with those of T. aestivum . They found that both lines activate celiac T cell response.…”
Section: Natural Varieties Of Cereal and Pseudocereals Suitable Fomentioning
confidence: 99%
“…If we consider, in fact, that for each genome (AA, BB and DD) there are dozens of genes coding for prolamins in wheat caryopses, it is evident that in Triticum monococcum the mere presence of the AA genome encodes for a reduced variety of gluten proteins (and of potential immune toxic peptides). Recent evidence shows that prolamins of some Triticum monococcum cause a reduced inflammatory effect in celiac patients [89,90,91,92], particularly for the inability to activate the innate branch of immune cells [89], or to induce apoptosis of enterocytes [93]. The reduced, or absent, toxicity of Triticum monococcum prolamins can then be interpreted in two ways, namely via ( i ) a low presence of toxic peptides; ( ii ) an abundant presence of protective sequences.…”
Section: Nutritional Quality Of Wheat Flour: Advantages In Introdumentioning
confidence: 99%